1990
DOI: 10.2136/sssaj1990.03615995005400040027x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Biopore Channels from Roots to Compression by Vertical Stresses

Abstract: The channels created in soil by roots and soil animals (biopores) play an important role in the subsequent movement of water, air, and new roots through irrigated clay soils in southeastern Australia. The maintenance of these biopores is critical for both crop productivity and erosion control. If these biopores are to remain open, they must be able to withstand the vertical stresses associated with vehicle and animal traffic. This study had three aims: (i) to examine the influence on porosity and permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 0 publications
3
31
1
1
Order By: Relevance
“…The minimum or no tillage plus the extensive tap-root system of the alfalfa would have promoted and protected the macropores, which would conduct water even in compacted soil. Blackwell et al (1990) demonstrated that biopore channels formed by alfalfa roots can be very stable at diameters >4 mm under stresses up to 200 kPa.…”
Section: Relationship Between Infiltration Rate and Bulk Densitymentioning
confidence: 99%
“…The minimum or no tillage plus the extensive tap-root system of the alfalfa would have promoted and protected the macropores, which would conduct water even in compacted soil. Blackwell et al (1990) demonstrated that biopore channels formed by alfalfa roots can be very stable at diameters >4 mm under stresses up to 200 kPa.…”
Section: Relationship Between Infiltration Rate and Bulk Densitymentioning
confidence: 99%
“…In a rotation, alfalfa reduces the input of N fertilizer for the succeeding annual crops while also improving seed yield and protein content (Badaruddin and Meyer 1990;Zentner et al 1990Zentner et al , 2001Entz et al 1995;Mohr et al 1999). It also helps to reduce soil salinity (Agriculture Canada 1991), soil erosion (Stinner and House 1989) and weed populations (Dryden et al 1983;Harvey and McNevin 1990), and improve soil moisture by snow trapping (Cutforth et al 2002), improving physical properties (Blackwell et al 1990) and organic matter . However, after about 3 years, the productivity of alfalfa stands tends to decline and the stands are terminated.…”
Section: Introductionmentioning
confidence: 99%
“…Soils restored from excavation material which was temporarily removed, for example during gravel exploitation, are particularly susceptible to compaction, as excavation, transport and repacking disrupt their structure and destabilize them (Lebert and Springob, 1994). Impacts on the macro-pores are of particular concern, as these structures play a crucial role for many soil processes such as drainage or aeration (Blackwell et al, 1990;Allaire-Leung et al, 2000).…”
Section: Introductionmentioning
confidence: 99%